Revisiting the Concept of Discrimination in Russian and Global Practice - Elena V. Kunts, Vladimir Y. Golubovsky, (Opción, 2019)
The aimIn this article, the legal nature of the concept and trends of discrimination both in the world and in domestic practice are considered via qualitative comparative research method. As a result, these inequalities are objectively emerging in politics, economics, becoming a reflection of global trends in the development of social relations, and they also generate social tensions in society, conflicts, and a reduction in various incentives for people at lower levels of the social hierarchy. In conclusion, the context of discrimination freedom and equality should be understood solely as legal categories, rather than social, economic or psychological benefits.